An efficient indirect plant regeneration from shoot apical meristem (SAM) derived embryogenic callus of Miscanthus × giganteus. (January 2023) - Sobańska, Karolina; Jedryszek, Piotr; Kern, Cameron; Basińska-Barczak, Aneta; Pniewski, Tomasz; Long, Stephen P.
Abstract: The perennial grass Miscanthus × giganteus with its high biomass and biofuel yields on marginal lands is a leading feedstock contender for future low carbon emission bioenergy production. Most M. x giganteus grown is from a sterile clone of a triploid form. Although this has the advantage that its production is not invasive, most plantings have had to be via rhizomes, which is time-consuming and expensive. Here we report an efficient micropropagation method via indirect plant regeneration from embryogenic callus developed from shoot apical meristem (SAM) explants of two field-grown elite M. × giganteus genotypes, Illinois and Ogi80. Following an optimized surface disinfection of field-grown stem, avoiding subsequent necrosis of explants, non-contaminated SAM in vitro culture was established. We successfully demonstrated in vitro differentiation of SAMs into somatic embryos on SCIM-22 medium, containing p-chlorophenoxyacetic acid and α-naphthalene acetic acid as growth regulators, which activity was synergistically amplified with activated charcoal, putrescine and 2-aminoindane-2-phosphonic acid. We observed 49% (Ogi80) and 82% (Illinois) embryogenic calli from the calli initiated, which developed into plantlets with 12% (Ogi80) and 33% (Illinois) of total regeneration efficiency after 15 weeks of culture. In vitro regenerated plants grown till maturity showed biometric traits comparable to rhizome-propagated plants, but in vitro regenerated plants of genotype Illinois were significantly superior regarding stem diameter, leaf width and tillering. This study is the first demonstration of somatic embryogenesis from vegetative tissues of field-harvested M. × giganteus resulting in propagation competitive with rhizome-propagated plants in terms of yield potential. Highlights: First evidence of somatic embryogenesis in callus dervied from shoot apical meristems (SAMs) of Miscanthus × giganteus . Optimized surface disinfection method developed for in vitro differentiation into somatic embryos from field-grown plants. M. × giganteus genotype determines the rate of re-differentiation of somatic embryos for plant regeneration. In vitro regenerated plants showed significantly superior growth vigor compared to rhizome propagated plants.